2016
DOI: 10.1016/j.jvs.2016.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Renal function changes after fenestrated endovascular aneurysm repair

Abstract: Acute and chronic renal dysfunction both occur in approximately one-quarter of patients after fEVAR; however, most of these cases are classified as mild according to consensus definitions of renal injury. The presence of mild or moderate baseline kidney disease should not preclude endovascular repair in the juxtarenal population. Routine biochemical analysis and branch vessel surveillance remain important aspects of clinical follow-up for patients undergoing fEVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 22 publications
2
20
1
Order By: Relevance
“…In addition, they concluded that increased surgical complexity was a risk factor for CIN. They suggested that minimizing surrogate markers for operative complexity is important (24). We also suggest that additional endovascular procedures should be performed in patients who have preoperative risk factors for CIN, including embolization of arteries separately from EVAR to minimize the complexity of the operation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, they concluded that increased surgical complexity was a risk factor for CIN. They suggested that minimizing surrogate markers for operative complexity is important (24). We also suggest that additional endovascular procedures should be performed in patients who have preoperative risk factors for CIN, including embolization of arteries separately from EVAR to minimize the complexity of the operation.…”
Section: Discussionmentioning
confidence: 95%
“…We strongly suspect that the increased amount of contrast medium administered in the embolization procedure was a cause of CIN development because, although the patients' characteristics and preoperative renal function did not differ significantly between the two groups, the contrast medium volume and CV/eGFR ratio were greater in patients undergoing simultaneous arterial embolization. Tran et al (24). reported that in patients who underwent fenestrated EVAR for juxtarenal or paravisceral aortic aneurysm, fluoroscopy time, operative time, and contrast volume were associated with the development of CIN.…”
Section: Discussionmentioning
confidence: 99%
“…Special care should be taken in those with already borderline renal function. 12,23,24 A relatively higher (non-significant) number of endoleaks was seen in the octogenarian group. As higher age involves greater peri-operative risk, it is possible that the treatment of octogenarian patients was done preferably with an endovascular approach over open surgical repair, despite more challenging anatomy, consequently leading to a slightly higher number of type I endoleaks.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have evaluated AKIs in patients undergoing FEVAR. [12][13][14][15][16] Acute and chronic kidney dysfunction appears to have occurred in approximately 25% of patients after FEVAR, but mild renal deterioration occurs in most cases. 14 The literature has described certain predictors of kidney injury after FEVAR, which include a preoperative renal length of <100 mm, prolonged operative duration, accessory renal artery thrombosis >2 mm, and occurrence of a perirenal hematoma in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) was defined as an absolute increase in serum creatinine concentration of $26.4 mmol/L or a percentage increase of $50% within 48 hours of completion of the procedure. [12][13][14][15][16] We then compared whether there was any significance in AKI in patients who had a bare-metal stent extension within a renal vessel vs those who did not.…”
Section: Methodsmentioning
confidence: 99%